Application of Adam Smith’s Four Canons in E-Commerce Tax Policy - ., Hendri (KnE Social Sciences, 2018)
The e-commerce business has its own character. With the Internet network as the backbone, the transaction process can be done quickly and practically. Different characteristics from the conventional trade proved to be a problem in itself, namely, the difficulty of establishing clear and fair tax rules. There are at least two things that become the problem of taxation caused by e-commerce transactions. The e-commerce transactions according to the OECD which are then adopted into the Directorate General of Taxation No. 62/PJ/2013 (SE-62) can be grouped into four groups: online marketplace, online retail, classified ads, and daily deals. The purpose of this research is to explain and describe the tax policy in Indonesia in the ecommerce business activities and the fulfillment of four cannon Adam smith for e-commerce business activities. The results show that taxes should be neutral and fair to the forms of e-commerce transactions and between conventional transactions and forms of e-commerce transactions. Business decisions should be based on economic motivation rather than tax and taxpayer considerations in the same situation and carrying out the same transaction should be taxed at the same rate. Efficiency of compliance costs by taxpayers and administrative costs of the tax authorities should be minimized. The tax provisions should be clear and easily (Certainty and Simplicity) understandable so that taxpayers can anticipate the tax consequences in the development of transactions including knowing when, where and how the tax should be calculated or paid. Taxation should produce the correct amount of tax in the right time (Effectiveness and Fairness). The potential for tax avoidance and smuggling should be minimized by still trying to anticipate proportionately to the activity. Keywords: tax, e-commerce, policy